WALTER BENJAMIN O LA HISTORIA A CONTRAPELO - Villena Fiengo, Sergio (2023)
This brief essay presents an interpretation of Walter Benjamin’s “Thesis on the Philosophy of History”. The author stresses the actuality of this already canonical text through the application of Benjamin’s own methodological principles as they pertain to a politically productive approach to history.